EFEKTIVITAS BUKU AJAR DIGITAL SISTEM EKSKRESI BERBASIS BRAIN-BASED LEARNING DILENGKAPI DENGAN AUGMENTED REALITY DAN COUPLE CARD DALAM MENINGKATKAN HASIL BELAJAR SISWA SMA - Amalia Nurul Imamah; Jekti Prihatin; Pujiastuti Pujiastuti (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2022)
In this 21st century, education has been growing rapidly in an aspect of knowledge. This increase in knowledge is supported by the application of digital media and technology. One of the uses of technology in education is digital textbooks. This technology is very helpful for online learning during the COVID-19 pandemic. Based on the digital textbook, Brain-Based Learning approach could be empowered student's brain potential as a whole in processing and thinking. This research aims to produce effective digital textbooks to increase the interest and learning outcomes of high school students. The design of the textbook development used refers to the ADDIE model (Analysis, Design, Development, Implementation, and Evaluations). The effectiveness of the developed digital textbooks has been seen based on the interest questionnaire and student learning outcomes. The average result of the student interest questionnaire was 86.65 with a very good category. The average value of Effect size is 0.66 with a medium effect category (Medium Effect).